2021
DOI: 10.21511/imfi.18(1).2021.23
|View full text |Cite
|
Sign up to set email alerts
|

Financial modeling trends for production companies in the context of Industry 4.0

Abstract: Over the years, technological progress has accelerated highly, and the speed, flexibility, human error reduction, and the ability to manage the process in real time have become more critical and required production companies to adapt production and business models according to the needs. The demand for real-time decision support systems adapted to these raising business needs is continuously growing. Nevertheless, businesses usually face challenges in identifying new indicators, data sources, and appropriate f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…In addition, most employees of enterprises that have digitized the provision of goods and services are confident that digital transformations (remote work, communication with customers through online communication, the introduction of high technology) will not be levelled even after the pandemic of COVID-19 (McKinsey & Company, 2020). In turn, the European Central Bank conducted a survey of 74 large non-financial companies, half of which produced goods, others were service providers to find out which digital technologies are used by large European companies to do business, the similar results were discussed by Kartanaitė et al (2021). The results showed that most of the surveyed companies use different digital technologies, among which the leading are big data analysis (87%) and cloud storage (82%).…”
Section: Literature Reviewmentioning
confidence: 96%
“…In addition, most employees of enterprises that have digitized the provision of goods and services are confident that digital transformations (remote work, communication with customers through online communication, the introduction of high technology) will not be levelled even after the pandemic of COVID-19 (McKinsey & Company, 2020). In turn, the European Central Bank conducted a survey of 74 large non-financial companies, half of which produced goods, others were service providers to find out which digital technologies are used by large European companies to do business, the similar results were discussed by Kartanaitė et al (2021). The results showed that most of the surveyed companies use different digital technologies, among which the leading are big data analysis (87%) and cloud storage (82%).…”
Section: Literature Reviewmentioning
confidence: 96%
“…The results showed that Ukrainian regions are different from each other both in terms of scientific-technical and production potentials and in terms of socio-economic development. Kartanaitė et al (2021) showed the necessity of assessment in forming a suggestion for decision-makers in the context of the innovation Industry 4.0.…”
Section: Literature Reviewmentioning
confidence: 99%
“…One of the reasons is that scientific and technological progress, transfer and commercialization of innovations, digitalization of economy and public management lead to more efficient use of labor and capital investments, increased productivity and ultimately to economic growth (Habenko, 2023;Alshourah et al, 2023). Moreover, technological progress and, accordingly, digital development has accelerated significantly over the years, and obvious advantages such as speed, flexibility, the ability to manage the process in real time, and the reduction of human errors have become even more in demand in the business environment, government, education, and other fields (Kartanaitė et al, 2021;Kiseľáková et al 2022;Stacho et al, 2023).…”
Section: Introductionmentioning
confidence: 99%